Nanomaterial-enhanced self-consolidating high-performance concrete: investigating the effects of nano POFA incorporation / Nuradila Izzaty Halim ... [et al.] - Halim, Nuradila Izzaty; Muhd Sidek, Muhd Norhasri; Newman, Aidan; Mohd Saman, Hamidah; Suliman, Nurul Huda; Mohd Fauzi, Mohd Afiq (UiTM Press, 2025)
Palm oil fuel ash (POFA) is one of the agricultural wastes that negatively impacts the environment and health because it is abundantly disposed of in landfills without commercial value. The primary objective of this research is to investigate the potential incorporation of Nano-POFA (NaPOFA) as a cement replacement into Self- Self-Consolidating HighPerformance Concrete (SCHPC) through an experimental study to produce concrete with improved durability and strength. The NaPOFA is prepared using high-energy milling and introduced as cement replacement from 1% - 10%. The evaluation of the SCHPC NaPOFA mix encompasses four tests: physical properties, assessed using a particle size analyser; fresh properties, evaluated through a flow table test; and mechanical properties, determined through a splitting tensile strength test, with supported software analysis on Design Expert. The results reveal that the optimal percentage of Nano-POFA replacement is 1%, resulting in an impressive 18.18% increase in flowability and a substantial 12.12% increase in splitting tensile strength compared to the control mix. In conclusion, the SCHPC NaPOFA mix developed in this study demonstrates potential applications for constructing durable and sustainable structures, contributing to reduced cement consumption and mitigating the carbon footprint in the construction industry.